Pericardial Effusion - Melioidosis or Tuberculosis (Journal of Medicine, 2012)
Melioidosis which is endemic in South East Asia and Northern Australia is now being reported from the Indian subcontinents as well. Meliodosis rarely presents as pericardial effusion. We report a case of B. pseudomallei causing pericardial effusion from India, where the most common infective cause of pericardial effusion is Mycobacterium tuberculosis. The chronic presentation of melioidosis is not unlike tuberculosis, and the clinician must have a high index of suspicion to diagnose meliodosis, especially in geographical areas where both tuberculosis and melioidosis are prevalent.DOI: http://dx.doi.org/10.3329/jom.v13i2.9368 J Medicine 2012; 13 : 230-232